A compound for organic electroluminescent material

By using binaphthalene-5-membered heterocyclic fused ring compound as the main material of the OLED device, the thermal stability and molecular orbital energy level are improved through group modification, the problem of limitations in the performance of the main material in the existing OLED technology is solved, and the performance of high efficiency and long-life OLED device is achieved.

CN119219656BActive Publication Date: 2025-03-14XIAN MANARECO NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411745016.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-14
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

In the existing OLED technology, the main material has limitations in performance and cannot meet the needs of higher quality OLED devices, especially in improving efficiency, brightness and service life.

Method used

The binaphthalene-5-membered heterocyclic fused ring compound is used as the parent core to modify the construction material through specific groups to improve the thermal stability and molecular orbital energy level of the compound, so as to be used as a blue or red light host material.

Benefits of technology

It significantly improves the efficiency, life and color purity performance of OLED devices, and realizes high-efficiency and long-life OLED devices applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219656B_ABST
    Figure CN119219656B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of organic light-emitting materials, and relates to a compound for organic electroluminescent materials. The present invention provides a class of di-naphtho-pentacyclic fused ring compounds, which are modified with a specific type of group so that they can be used as a blue light host material or a red light host material in an organic electroluminescent device, and play a significant role in improving the performance of the device. When the compound provided by the present invention is used as a host material in the light-emitting layer of an organic electroluminescent device, it can effectively improve the brightness efficiency or life of the device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic luminescent materials and relates to a compound used for organic electroluminescent materials. Background Art

[0002] Organic electroluminescent elements (OLEDs) have developed rapidly as a solid-state light-emitting technology and have gradually achieved industrial application. The basic structure of an OLED element usually includes multiple layers such as an anode, a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, a hole blocking layer, an electron transport layer, an electron injection layer, and a cathode. Under the action of an external electric field, the physical process inside the device is as follows: holes are injected from the anode into the organic layer, and electrons are injected from the cathode into the organic layer. When these injected holes and electrons meet in the light-emitting layer, they combine to form excitons. When the excitons re-transition to the ground state, energy is released, and this energy is emitted in the form of light, thereby achieving a luminous effect.

[0003] However, in order to further improve the key optoelectronic properties of OLED devices, such as efficiency, brightness, and service life, the industry usually dopes the luminescent material into a specific host material. The main purpose of this practice is to reduce the exciton quenching effect, thereby optimizing the luminescence performance of the device. Exciton quenching refers to the phenomenon that the exciton loses energy prematurely during the luminescence process due to various reasons (such as interaction with impurities, defects or other excitons), resulting in reduced brightness efficiency. By doping the luminescent material into a suitable host material, this quenching effect can be effectively reduced, thereby improving the overall performance of the device.

[0004] Therefore, high-performance host materials are crucial to obtaining high-quality OLED device performance. It not only needs to have good carrier transport properties to ensure that holes and electrons can be efficiently injected into the light-emitting layer, but also needs to have a low exciton quenching rate to ensure that the excitons can emit light stably. However, how to develop high-quality host materials that meet these requirements and have good stability has always been a difficult and hot issue in the field of OLED technology. At present, although some host materials have been developed and applied to OLED devices, they still have certain limitations in performance and cannot meet the growing demand for higher quality OLED devices. Summary of the invention

[0005] In view of the deficiencies in the prior art and the need for improvement, the present invention uses a dinaphthoic five-membered heterocyclic fused ring compound as the mother core. Due to the unique molecular conjugated structure within the molecule, it has high thermal stability. The material constructed after appropriate group modification can obtain a better frontier orbital energy level and is applied as a blue light host or red light host material, which plays a key role in improving the device efficiency, life, color purity and other performance.

[0006] In one aspect, the present invention relates to a compound having a structure as shown in formula (I):

[0007] ;

[0008] Wherein, X is O or S;

[0009] Y is one of O, S, and CR1R2;

[0010] L is a single bond, a substituted or unsubstituted phenyl group, a substituted or unsubstituted naphthyl group, a substituted or unsubstituted anthracenyl group, a substituted or unsubstituted pyrene group, or a substituted or unsubstituted C6-C30 arylene group;

[0011] Ar is substituted or unsubstituted benzene, substituted or unsubstituted condensed polycyclic aromatic group, substituted or unsubstituted electron donating group, substituted or unsubstituted electron withdrawing group;

[0012] The R1 is methyl or phenyl;

[0013] The R2 is a methyl group or a phenyl group;

[0014] Either hydrogen atom is deuterated or not.

[0015] Furthermore, in the compounds provided by the present invention, they have the chemical structures shown in Formula A1-A6,

[0016] .

[0017] Furthermore, in the compounds provided by the present invention, any of the substitutions or unsubstitutions is represented by one of no substitution, a monosubstituent, a disubstituent, a trisubstituent, and a tetrasubstituent.

[0018] Illustratively, in the compounds provided by the present invention, the substituents in the monosubstituent, disubstituent, trisubstituent, and tetrasubstituent are selected from the following groups:

[0019]

[0020] Furthermore, in the compound provided by the present invention, the fused polycyclic aromatic group is one of naphthyl, anthracenyl, pyrene, triphenylenyl, chrysene, and phenanthrenyl.

[0021] Furthermore, in the compound provided by the present invention, the electron donating group is an amine derivative or a carbazole derivative.

[0022] Furthermore, in the compound provided by the present invention, the electron-withdrawing group is one of a triazine group, a pyrimidine group, a pyrazine group, an imidazolyl group, and a pyridyl group.

[0023] Furthermore, in the compounds provided by the present invention, Ar is substituted by an aryl group, a N-containing heteroaryl group, an O-containing heteroaryl group, or an S-containing heteroaryl group.

[0024] Furthermore, in the compounds provided by the present invention, L is phenyl, naphthyl, anthracenyl, or pyrene.

[0025] Further, in the compounds provided by the present invention, Ar is phenyl, naphthyl, anthracenyl, pyrene, phenanthryl, triphenylene radical, substituted or unsubstituted amine, substituted or unsubstituted carbazolyl, substituted or unsubstituted furanyl, substituted or unsubstituted thienyl, substituted or unsubstituted triazine, substituted or unsubstituted pyrimidinyl, substituted or unsubstituted pyrazinyl, substituted or unsubstituted pyridyl, substituted or unsubstituted benzimidazolyl.

[0026] Furthermore, in the compounds provided by the present invention, the structures shown in Compound 1 to Compound 200 are as follows,

[0027] ;

[0028] Here, D indicates that the hydrogen atom is deuterated.

[0029] Illustratively, D1-D25 in compound 51 indicates that 1 to 25 hydrogen atoms in the compound of this formula are deuterated.

[0030] In another aspect, the present invention relates to use of the compound in an organic electroluminescent device or an organic electroluminescent apparatus.

[0031] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects or advantages:

[0032] The present invention constructs a condensed ring structure with certain rigidity and molecular distortion by connecting a bis-naphtho-pentacyclic heterocyclic mother core with condensed ring molecules such as pyrene, triphenylene, chrysene, phenanthrene, etc. at a specific position, thereby improving the thermal stability of the compound, and as a blue light main material, improving the efficiency, life and other properties of the organic electroluminescent material. The bis-naphtho-pentacyclic heterocyclic mother core is connected with an electron-donating group such as a substituted or unsubstituted amino derivative, a substituted or unsubstituted carbazole derivative, or with an electron-withdrawing group such as a substituted or unsubstituted triazine group, a substituted or unsubstituted pyrimidine group, a substituted or unsubstituted pyrazinyl group, a substituted or unsubstituted imidazole group, a substituted or unsubstituted pyridine group, etc. at a specific position, which can optimize the material molecular orbital energy level, further improve the triplet energy of the compound, and as a red light main material, can significantly improve the performance of the light-emitting device, and achieve high efficiency and long life. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 Schematic diagram of the structure of an organic electroluminescent element.

[0035] Among them, 1 is the substrate, 2 is the anode layer, 3 is the hole injection layer, 4 is the first hole transport layer, 5 is the second hole transport layer, 6 is the light emitting layer, 7 is the hole blocking layer, 8 is the electron transport layer, 9 is the electron injection layer, and 10 is the cathode layer. DETAILED DESCRIPTION

[0036] The technical scheme of the present invention is described below in conjunction with the examples, but the present invention is not limited to the following examples. The experimental methods and detection methods described in each example are conventional methods unless otherwise specified; the reagents and materials are available on the market unless otherwise specified, and the % in the following examples are all mass percentages unless otherwise specified.

[0037] Synthesis Example 1, Synthesis of Intermediate 1:

[0038]

[0039] Synthesis Example 2, Synthesis of Intermediate 1-3:

[0040] Under nitrogen protection, intermediate 1-1 (100.0 g, 0.53 mol), intermediate 1-2 (191.6 g, 0.58 mol), tetrakis(triphenylphosphine palladium) (3.0 g, 2.63 mmol), potassium carbonate (109.0 g, 0.79 mol), tetrabutylammonium bromide (3.4 g, 10.53 mmol), toluene (1.6 L), ethanol (500 mL), pure water (250 mL) were added to a three-necked flask. The reaction flask was replaced with nitrogen three times and then heated to 80 °C for 8 h. The reaction solution was cooled to room temperature and washed with water until neutral. The organic phase was dried over anhydrous sodium sulfate and concentrated, and purified by silica gel column to obtain 132.1 g of intermediate 1-3 with a yield of 71.9%.

[0041] Synthesis Example 3, Synthesis of Intermediates 1-4:

[0042] Add intermediate 1-3 (130.0 g, 0.37 mol) and dichloromethane (1.5 L) to a dry three-necked flask, cool the reaction system to -5~0 °C using an ice-salt bath, drop boron tribromide (373.1 g, 1.49 mol), stir at room temperature for 6 h, and then pour into ice water to quench the reaction. The organic phase was then washed with water until neutral, dried over anhydrous sodium sulfate, concentrated, and purified by silica gel column to obtain 97.7 g of intermediate 1-4 with a yield of 78.3%.

[0043] Synthesis Example 4, Synthesis of Intermediates 1-5:

[0044] Add intermediate 1-4 (95.0 g, 0.28 mol), potassium carbonate (78.2 g, 0.57 mol), and N,N-dimethylformamide (1 L) to a dry three-necked flask, and heat to 120 °C for 4 h. After the reaction solution is cooled to room temperature, pour it into water under stirring to precipitate solids. After filtering, the filter cake is completely dissolved in toluene, and then washed with water until neutral. The organic phase is dried over anhydrous sodium sulfate and concentrated, and purified by silica gel column to obtain 72.9 g of intermediate 1-5 with a yield of 81.6%.

[0045] Synthesis Example 5, Synthesis of Intermediate 1-7:

[0046] Under nitrogen protection, intermediate 1-5 (40.0 g, 0.13 mol), intermediate 1-6 (33.0 g, 0.14 mol), tetrakis(triphenylphosphine palladium) (0.73 g, 0.63 mmol), potassium carbonate (26.3 g, 0.19 mol), tetrabutylammonium bromide (0.82 g, 2.54 mmol), toluene (1 L), ethanol (400 mL), pure water (200 mL) were added to a three-necked flask. The reaction flask was replaced with nitrogen three times and then heated to 80 °C for 8 h. The reaction solution was cooled to room temperature and washed with water until neutral. The organic phase was dried over anhydrous sodium sulfate and concentrated, and purified by silica gel column to obtain 36.5 g of intermediate 1-7 with a yield of 67.4%.

[0047] Synthesis Example 6, Synthesis of Intermediates 1-8:

[0048] Add intermediate 1-7 (35.0 g, 82.0 mmol) and dichloromethane (700 mL) to a dry three-necked flask, cool the reaction system to -5~0 °C using an ice-salt bath, drop boron tribromide (61.6 g, 0.24 mol), stir at room temperature for 6 h, and pour into ice water to quench the reaction. The organic phase was then washed with water until neutral, dried over anhydrous sodium sulfate, concentrated, and purified by silica gel column to obtain 28.8 g of intermediate 1-8 with a yield of 85.1%.

[0049] Synthesis Example 7, Synthesis of Intermediate 1:

[0050] Add intermediate 1-8 (27.0 g, 65.4 mmol), potassium carbonate (18.0 g, 0.13 mol), N,N-dimethylformamide (0.5 L) to a dry three-necked flask, and heat to 120 °C for 4 h. After the reaction solution was cooled to room temperature, it was poured into water under stirring to precipitate solids. After filtering, the filter cake was completely dissolved in toluene, and then washed with water until neutral. The organic phase was dried over anhydrous sodium sulfate and concentrated, and purified by silica gel column to obtain 20.5 g of intermediate 1 with a yield of 79.7%.

[0051] Synthesis Example 8, Synthesis of Intermediate 2:

[0052]

[0053] Synthesis Example 9, Synthesis of Intermediate 2-2:

[0054] According to the synthesis method of intermediate 1-7, intermediate 1-6 was replaced by intermediate 2-1, and the yield was 73.7%.

[0055] Synthesis Example 10, Synthesis of Intermediate 2-3:

[0056] According to the synthesis method of intermediate 1-8, intermediate 1-7 was replaced by intermediate 2-2, with a yield of 83.9%.

[0057] Synthesis Example 11, Synthesis of Intermediate 2:

[0058] According to the synthesis method of intermediate 1, intermediate 1-8 was replaced by intermediate 2-3, with a yield of 71.6%.

[0059] Synthesis Example 12, Synthesis of Intermediate 3:

[0060]

[0061] Synthesis Example 13, Synthesis of Intermediate 3-3:

[0062] According to the synthesis method of intermediate 1-3, intermediate 1-1 was replaced by intermediate 3-1, and intermediate 1-2 was replaced by intermediate 3-2, with a yield of 75.3%.

[0063] Synthesis Example 14, Synthesis of Intermediate 3-4:

[0064] Under nitrogen protection, add intermediate 3-3 (70.0 g, 0.19 mol) and tetrahydrofuran (600 mL) to a three-necked flask, add methylmagnesium bromide (1.0 M in THF, 584.6 mL) dropwise under stirring at room temperature, and heat to 50 ° C for 3 h after the addition is complete. After the reaction solution is cooled to room temperature, add ammonium chloride aqueous solution to quench the reaction, adjust the pH to weak acidity and wash with water to neutrality, dry the organic phase with anhydrous sodium sulfate, concentrate, and purify on a silica gel column to obtain 45.6 g of intermediate 3-4 with a yield of 65.2%.

[0065] Synthesis Example 15, Synthesis of Intermediate 3-5:

[0066] Under nitrogen protection, intermediate 3-4 (45.0 g, 0.12 mol), methanesulfonic acid (24.1 g, 0.25 mol), and toluene (500 mL) were added to a three-necked flask and heated to 110°C for 3 h. The reaction solution was cooled to room temperature and washed with water until neutral. The organic phase was dried over anhydrous sodium sulfate and concentrated, and purified by silica gel column to obtain 31.7 g of intermediate 3-5 with a yield of 74.2%.

[0067] Synthesis Example 16, Synthesis of Intermediate 3-6:

[0068] According to the synthesis method of intermediate 1-7, intermediate 1-5 was replaced by intermediate 3-5, with a yield of 69.5%.

[0069] Synthesis Example 17, Synthesis of Intermediate 3-7:

[0070] According to the synthesis method of intermediate 1-8, intermediate 1-7 was replaced by intermediate 3-6, with a yield of 80.6%.

[0071] Synthesis Example 18, Synthesis of Intermediate 3:

[0072] According to the synthesis method of intermediate 1, intermediate 1-8 was replaced by intermediate 3-7, with a yield of 76.1%.

[0073] Synthesis Example 19, Synthesis of Intermediate 4:

[0074]

[0075] Synthesis Example 20, Synthesis of Intermediate 4-1:

[0076] According to the synthesis method of intermediate 3-6, intermediate 1-6 was replaced by intermediate 2-1, and the yield was 67.9%.

[0077] Synthesis Example 21, Synthesis of Intermediate 4-2:

[0078] According to the synthesis method of intermediate 3-7, intermediate 3-6 was replaced by intermediate 4-1, with a yield of 77.2%.

[0079] Synthesis Example 22, Synthesis of Intermediate 4:

[0080] According to the synthesis method of intermediate 3, intermediate 3-7 was replaced by intermediate 4-2, with a yield of 75.8%.

[0081] Synthesis Example 23, Synthesis of Intermediate 5:

[0082]

[0083] Synthesis Example 24, Synthesis of Intermediate 5-2:

[0084] According to the synthesis method of intermediate 1-3, intermediate 1-2 was replaced by intermediate 5-1, with a yield of 73.3%.

[0085] Synthesis Example 25, Synthesis of Intermediate 5-3:

[0086] According to the synthesis method of intermediate 1-4, intermediate 1-3 was replaced by intermediate 5-2, with a yield of 82.6%.

[0087] Synthesis Example 26, Synthesis of Intermediate 5-4:

[0088] According to the synthesis method of intermediate 1-5, intermediate 1-4 was replaced by intermediate 5-3, with a yield of 68.2%.

[0089] Synthesis Example 27, Synthesis of Intermediate 5-5:

[0090] According to the synthesis method of intermediate 1-7, intermediate 1-5 was replaced by intermediate 5-4, with a yield of 70.9%.

[0091] Synthesis Example 28, Synthesis of Intermediate 5-6:

[0092] According to the synthesis method of intermediate 1-8, intermediate 1-7 was replaced by intermediate 5-5, with a yield of 78.5%.

[0093] Synthesis Example 29, Synthesis of Intermediate 5:

[0094] According to the synthesis method of intermediate 1, intermediate 1-8 was replaced by intermediate 5-6, with a yield of 72.1%.

[0095] Synthesis Example 30, Synthesis of Intermediate 6:

[0096]

[0097] Synthesis Example 31, Synthesis of Intermediate 6-1:

[0098] According to the synthesis method of intermediate 5-5, intermediate 1-6 was replaced by intermediate 2-1, with a yield of 74.2%.

[0099] Synthesis Example 32, Synthesis of Intermediate 6-2:

[0100] According to the synthesis method of intermediate 5-6, intermediate 5-5 was replaced by intermediate 6-1, with a yield of 79.3%.

[0101] Synthesis Example 33, Synthesis of Intermediate 6:

[0102] According to the synthesis method of intermediate 5, intermediate 5-6 was replaced by intermediate 6-2, with a yield of 72.8%.

[0103] Synthesis Example 34, Synthesis of Compound 51-A:

[0104]

[0105] Under nitrogen protection, intermediate 1 (5.0 g, 12.7 mmol), intermediate 51-1 (3.6 g, 13.4 mmol), sodium tert-butoxide (3.7 g, 38.2 mmol), Pd2(dba)3 (0.12 g, 0.13 mmol), XantPhos (0.15 g, 0.25 mmol) and toluene (200 mL) were added to the reaction flask in sequence and heated to reflux for 8 h. After the reaction was completed, the system was cooled to room temperature and washed with water until neutral. The organic phase was dried over anhydrous sodium sulfate and purified by silica gel column. The column liquid was concentrated and recrystallized with an appropriate amount of toluene to obtain 5.4 g of compound 51-A with a yield of 68.1%.

[0106] The mass spectrometry results of the obtained samples are: HR-MS (APCI): m / z 628.2538 [M+H] + ;

[0107] Calculated value for C44H13O3ND12 (%): C, 84.20; H, 5.92; O, 7.65; N, 2.23; Found: C, 84.18; H, 5.91; O, 7.66; N, 2.25.

[0108] Synthesis Example 35, Synthesis of Compound 53-A:

[0109]

[0110] According to the synthesis method of compound 51-A, the raw material intermediate 1 was replaced by intermediate 3, and the yield was 66.7%.

[0111] The mass spectrometry results of the obtained samples are: HR-MS (APCI): m / z 654.3361 [M+H] + ;

[0112] Calculated for C47H19O2ND12 (%): C, 86.36; H, 6.60; O, 4.90; N, 2.14; Found: C, 86.33; H, 6.60; O, 4.92; N, 2.15.

[0113] Synthesis Example 36, Synthesis of Compound 56-A:

[0114]

[0115] According to the synthesis method of compound 51-A, the raw material intermediate 51-1 was replaced with intermediate 56-1, with a yield of 71.3%.

[0116] The mass spectrometry results of the obtained samples are: HR-MS (APCI): m / z 616.2409 [M+H] + ;

[0117] Calculated value for C44H13O2ND14 (%): C, 85.85; H, 6.68; O, 5.20; N, 2.27; Found: C, 85.83; H, 6.68; O, 5.21; N, 2.28.

[0118] Synthesis Example 37, Synthesis of Compound 57-A:

[0119]

[0120] According to the synthesis method of compound 51-A, the raw material intermediate 1 was replaced by intermediate 5, and intermediate 51-1 was replaced by intermediate 56-1, with a yield of 74.6%.

[0121] The mass spectrometry results of the obtained samples are: HR-MS (APCI): m / z 632.2195 [M+H] + ;

[0122] Calculated value for C44H13ONSD14 (%): C, 83.66; H, 6.51; O, 2.53; N, 2.22; S, 5.08; Found value: C, 83.68; H, 6.50; O, 2.52; N, 2.23; S, 5.07.

[0123] Synthesis Example 38, Synthesis of Compound 81-A:

[0124]

[0125] Under nitrogen protection, intermediate 1 (5.0 g, 12.7 mmol), intermediate 81-1 (4.2 g, 13.4 mmol), tetrakis(triphenylphosphine palladium) (0.30 g, 0.13 mmol), potassium carbonate (2.6 g, 19.1 mmol), tetrabutylammonium bromide (0.1 g, 0.31 mmol), toluene (100 mL), ethanol (40 mL), pure water (20 mL) were added to a three-necked flask. The reaction flask was replaced with nitrogen three times and then heated to 80 °C for 6 h. The reaction solution was cooled to room temperature and washed with water until neutral, dried over anhydrous sodium sulfate, concentrated, and purified by recrystallization from toluene to obtain 5.7 g of compound 81-A with a yield of 71.5%.

[0126] The mass spectrometry results of the obtained samples are: HR-MS (APCI): m / z 624.2325 [M+H] + ;

[0127] Calculated value for C46H13O2D13 (%): C, 88.60; H, 6.27; O, 5.13; Found: C, 88.63; H, 6.25; O, 5.12.

[0128] Synthesis Example 39, Synthesis of Compound 82-A:

[0129]

[0130] According to the synthesis method of compound 81-A, the raw material intermediate 1 was replaced by intermediate 5, and the yield was 73.9%.

[0131] The mass spectrometry results of the obtained samples are: HR-MS (APCI): m / z 640.2856 [M+H] + ;

[0132] Calculated value for C46H13OSD13 (%): C, 86.37; H, 6.12; O, 2.50; S, 5.01; Found: C, 86.38; H, 6.10; O, 2.52; S, 5.00.

[0133] Synthesis Example 40, Synthesis of Compound 91-A:

[0134]

[0135] According to the synthesis method of compound 81-A, the raw material intermediate 81-1 was replaced by intermediate 91-1, with a yield of 67.6%.

[0136] The mass spectrometry results of the obtained samples are: HR-MS (APCI): m / z 568.2619 [M+H] + ;

[0137] Calculated value for C42H13O2D9 (%): C, 88.88; H, 5.48; O, 5.64; Found: C, 88.86; H, 5.46; O, 5.68.

[0138] Synthesis Example 41, Synthesis of Compound 92-A:

[0139]

[0140] According to the synthesis method of compound 81-A, the raw material intermediate 1 was replaced by intermediate 5, and intermediate 81-1 was replaced by intermediate 91-1, with a yield of 65.8%.

[0141] The mass spectrometry results of the obtained samples are: HR-MS (APCI): m / z 584.2576 [M+H] + ;

[0142] Calculated value for C42H13OSD9 (%): C, 86.44; H, 5.33; O, 2.74; S, 5.49; Found: C, 86.47; H, 5.28; O, 2.73; S, 5.52.

[0143] Synthesis Example 42, Synthesis of Compound 151:

[0144]

[0145] According to the synthesis method of compound 81-A, the raw material intermediate 1 was replaced by intermediate 2, and intermediate 81-1 was replaced by intermediate 151-1, with a yield of 75.9%.

[0146] The mass spectrometry results of the obtained samples are: HR-MS (APCI): m / z 716.3253 [M+H] + ;

[0147] Calculated for C51H29O2N3 (%): C, 85.58; H, 4.08; O, 4.47; N, 5.87; Found: C, 85.63; H, 4.06; O, 4.46; N, 5.85.

[0148] Synthesis Example 43, Synthesis of Compound 152:

[0149]

[0150] According to the synthesis method of compound 81-A, the raw material intermediate 1 was replaced by intermediate 6, and intermediate 81-1 was replaced by intermediate 151-1, with a yield of 71.6%.

[0151] The mass spectrometry results of the obtained samples are: HR-MS (APCI): m / z 682.2618 [M+H] + ;

[0152] C47H27ON3S (%) calculated: C, 82.80; H, 3.99; O, 2.35; N, 6.16; S, 4.70; found: C, 82.83; H, 3.97; O, 2.33; N, 6.18; S, 4.69.

[0153] Synthesis Example 44, Synthesis of Compound 161:

[0154]

[0155] According to the synthesis method of compound 81-A, the raw material intermediate 1 was replaced by intermediate 2, and intermediate 81-1 was replaced by intermediate 161-1, with a yield of 73.3%.

[0156] The mass spectrometry results of the obtained samples are: HR-MS (APCI): m / z 756.2823 [M+H] + ;

[0157] Calculated for C53H29O3N3 (%): C, 84.22; H, 3.87; O, 6.35; N, 5.56; Found: C, 84.23; H, 3.84; O, 6.34; N, 5.59.

[0158] Synthesis Example 45, Synthesis of Compound 163:

[0159]

[0160] According to the synthesis method of compound 81-A, the raw material intermediate 1 was replaced by intermediate 4, and intermediate 81-1 was replaced by intermediate 161-1, with a yield of 69.4%.

[0161] The mass spectrometry results of the obtained samples are: HR-MS (APCI): m / z 782.3059 [M+H] + ;

[0162] Calculated for C56H35O2N3 (%): C, 86.02; H, 4.51; O, 4.09; N, 5.38; Found: C, 86.06; H, 4.48; O, 4.07; N, 5.39.

[0163] Except for compound 51-A, compound 53-A, compound 56-A, compound 57-A, compound 81-A, compound 82-A, compound 91-A, compound 92-A, compound 151, compound 152, compound 161 and compound 163 disclosed in the present invention, other compounds can be prepared by referring to the above preparation method.

[0164] Simulation Calculation Example

[0165] This example provides HOMO, LUMO, and triplet energy simulation calculations of Compound 51-A, Compound 53-A, Compound 56-A, Compound 57-A, Compound 81-A, Compound 82-A, Compound 91-A, Compound 92-A, Compound 151, Compound 152, Compound 161, Compound 163, and existing blue light emitting layer host material BH1, red light host material RH1, RH2. HOMO and LUMO are data obtained from simulation calculations, and the calculation method uses B3LYP hybrid functional, basis set 6-31g (d, P), and the results are shown in Table 1.

[0166] Table 1. T1 energy level and HOMO, LUMO simulation calculation results

[0167]

[0168] As shown in Table 1, the compounds disclosed in the present invention have relatively suitable HOMO, LUMO, and T1 values, and these compounds are suitable for use as blue light host or red light host materials. The present invention uses the dinaphtho-pentacyclic fused ring compound in OLED devices to effectively improve the brightness efficiency and service life of the device.

[0169] Taking some compounds provided by the present invention as examples, the compounds are applied as blue light or red light host materials to organic electroluminescent devices to verify the excellent effects achieved.

[0170] The excellent effect of the OLED material of the present invention in the device is specifically described in detail through the device performance of device embodiments 1 to 24 and comparative examples 1 and 2. The structure and manufacturing process of device embodiments 1 to 8 of the present invention and comparative example 1 are exactly the same, except that the main material of the light-emitting layer is replaced; the structure and manufacturing process of device embodiments 9 to 24 and comparative example 2 are exactly the same, except that the main material of the light-emitting layer is replaced, and the doping concentration of the light-emitting material RD01 is 5%. The same glass substrate and electrode material are used in the device preparation, and the film thickness of the electrode material is also kept consistent, as follows.

[0171] Device Example 1

[0172] This embodiment provides an organic electroluminescent device, the structure of which is as follows: Figure 1 As shown, it includes a substrate 1, an anode layer 2, a hole injection layer 3, a first hole transport layer 4, a second hole transport layer 5, a light emitting layer 6, a hole blocking layer 7, an electron transport layer 8, an electron injection layer 9 and a cathode layer 10 which are stacked in sequence.

[0173] Among them, the material of the anode layer 2 is indium tin oxide (ITO) with a high work function, the material of the hole injection layer 3 is HAT-CN with a thickness of 5nm; the material of the first hole transport layer 4 is HT1 with a thickness of 60nm; the material of the second hole transport layer 5 is HT2 with a thickness of 15nm; the light-emitting layer 6 uses compound 81-A as the main material and BD01 as the light-emitting material, with a doping mass ratio of 2% and a thickness of 30nm; the material of the hole blocking layer 7 is HB with a thickness of 10nm; the material of the electron transport layer 8 is ET-1 with a thickness of 30nm; the material of the electron injection layer 9 is Liq with a thickness of 2nm; the material of the cathode layer 10 is Al with a thickness of 100nm.

[0174] The basic material structure used in each functional layer of the device is as follows:

[0175]

[0176]

[0177] The specific preparation steps of the above organic electroluminescent device are as follows:

[0178] 1) Clean the ITO anode on the transparent glass or plastic substrate by ultrasonic cleaning with deionized water, acetone, and ethanol for 20 minutes each, and then perform plasma treatment in an oxygen atmosphere for 5 minutes;

[0179] 2) On the ITO anode layer, the hole injection layer material HAT-CN is deposited by vacuum evaporation with a thickness of 5 nm. This layer serves as the hole injection layer;

[0180] 3) Vacuum evaporation of hole transport material HT1 on the hole injection layer with a thickness of 60 nm, which serves as the first hole transport layer;

[0181] 4) Vacuum evaporation is performed on the first hole transport layer HT1 to deposit a hole transport material HT2 with a thickness of 15 nm, and this layer serves as the second hole transport layer;

[0182] 5) On the second hole transport layer, a light-emitting layer was co-deposited by vacuum evaporation, using compound 81-A as the main material and BD01 as the light-emitting material, with a doping mass ratio of 2% and a thickness of 30 nm;

[0183] 6) On the light-emitting layer, a hole blocking material HB is deposited by vacuum evaporation with a thickness of 10 nm. This layer serves as a hole blocking layer.

[0184] 7) On the hole blocking layer, the electron transport material ET-1 is deposited by vacuum evaporation with a thickness of 30 nm. This layer serves as the electron transport layer.

[0185] 8) On the electron transport layer, the electron injection material Liq is evaporated by vacuum evaporation with a thickness of 2 nm. This layer serves as the electron injection layer;

[0186] 9) On the electron injection layer, cathode Al is deposited by vacuum evaporation with a thickness of 100 nm. This layer is used as a cathode conductive electrode.

[0187] The implementation process of device examples 2 to 8 is the same as that of device example 1, except that the main material of the light-emitting layer is replaced by other developed compounds instead of compound 81-A, and device examples 1 to 8 are blue light devices.

[0188] Device Examples 9 to 24 are red light devices, and the implementation process is the same as that of Example 1 except for the light-emitting layer. The light-emitting layer adopts a three-source co-evaporation technology, that is, the first host, the second host, and the light-emitting material RD01 are simultaneously evaporated at different rates, the mass ratio of the first host to the second host is 1:1, and the mass ratio of RD01 is 5%. The first host and the second host materials of Device Examples 9 to 24 are compounds developed in this application.

[0189] Comparative Example 1

[0190] The same as device embodiment 1, except that BH1 is used as the main material of the blue light emitting layer instead of compound 81-A.

[0191] Comparative Example 2

[0192] The same as device embodiment 1, except that: the first host RH1 and the second host RH2 of the red light emitting layer are co-evaporated with the light emitting material RD01 in a ratio of 1:1, and the doping concentration of RD01 is 5%.

[0193] The components of different devices prepared in device embodiments 1 to 24, comparative example 1, and comparative example 2 of the present invention are shown in Table 2:

[0194] Table 2, Comparison of the components of the light-emitting layers of various device examples

[0195]

[0196] The cathode and anode of each group of organic electroluminescent devices were connected by a known driving circuit, and the voltage-efficiency-current density relationship of the OLED device was tested by a standard method using a Keithley 2400 power supply combined with a PR670 photometer; the life of the blue and red light devices was tested by a constant current method under the condition of applying 20 mA / cm 2 Under the current density, the initial brightness of the device is 100%, and the time required for the brightness to decay to 90% of the initial brightness is the LT90 life of the device; the test results are shown in Table 3.

[0197] Table 3, Performance results of organic electroluminescent devices in each group

[0198]

[0199] As shown in Table 3, the compounds provided by the present invention are applied to OLED devices as blue or red light main materials, and have excellent performance. For example, the compound 101 in Example 5 of the blue light device is used as a blue light main material, and compared with BH1 in Comparative Example 1, the brightness efficiency and service life are significantly improved, the brightness efficiency is increased by 20.1%, and the device life is increased by 43.5%; the deuterated hole-type red light main material compound 61 is compared with the comparative material RH1, the device brightness efficiency is increased by 44.6%, and the device life is increased by 50.2%; the deuterated electron-type red light main material compound 136 is compared with the comparative material RH2, the device brightness efficiency is increased by 45.7%, and the device life is increased by 52.5%. It can be seen that the compounds of the present invention are selected as the main materials of the blue or red light emitting layer, and compared with the existing materials applied to OLED light-emitting devices, the brightness efficiency and life performance of the device are greatly improved, which has great application value in the application of OLED devices and has good industrialization prospects.

[0200] The present invention provides a bis-naphtho-pentacyclic fused ring compound and an organic electroluminescent device thereof, which fully utilizes the rigidity and molecular distortion of the bis-naphtho-pentacyclic fused ring to improve the triplet energy and glass transition temperature of the material, and further modifies the compound with fused ring molecules such as anthracene and pyrene or typical electron-donating groups or typical electron-withdrawing groups on this basis, so as to optimize the frontier orbital energy level and triplet energy of the compound, thereby satisfying the application of blue light main body or red light main body material, and achieving high efficiency and long life of the device. It can be seen that the bis-naphtho-pentacyclic mother nucleus can obtain compounds of different properties by modifying substituents of different properties, thereby achieving multifunctional applications. The series of compounds provided by the present invention show excellent performance as the main material of the blue light or red light emitting layer in the organic electroluminescent (OLED) device, and have a significant effect on improving the efficiency and life of the device.

[0201] As described above, the basic principle, main features and advantages of the present invention are well described. The above embodiments and descriptions are only descriptions of the preferred implementation modes of the present invention, and the present invention is not limited by the above embodiments. Without departing from the spirit and scope of the present invention, various changes and improvements made by ordinary technicians in this field to the technical solution of the present invention should fall within the protection scope determined by the present invention.

Claims

1. A compound, characterized in that Having a structure as shown in formula (I), ; Wherein, X is O or S; Y is one of O, S, and CR1R2; L is one of a single bond, a substituted or unsubstituted phenyl group, and a substituted or unsubstituted C6-C30 arylene group; Ar is a substituted or unsubstituted electron-donating group, a substituted or unsubstituted electron-withdrawing group; The electron-donating group is an amine derivative or a carbazole derivative; The electron-withdrawing group is one of triazine, pyrimidine, pyrazine, imidazolyl, and pyridyl; The R1 is methyl or phenyl; The R2 is a methyl group or a phenyl group; Either hydrogen atom is deuterated or not.

2. The compound according to claim 1, characterized in that Any of the substitutions or unsubstitutions mentioned above refers to one of no substitution, a monosubstituent, a disubstituent, a trisubstituent, and a tetrasubstituent.

3. The compound according to claim 1, characterized in that The Ar is substituted by an aryl group, a N-containing heteroaryl group, an O-containing heteroaryl group, or a S-containing heteroaryl group.

4. The compound according to claim 1, characterized in that The Ar is a substituted or unsubstituted amine group, a substituted or unsubstituted carbazolyl group, a substituted or unsubstituted furyl group, a substituted or unsubstituted thienyl group, a substituted or unsubstituted triazine group, a substituted or unsubstituted pyrimidinyl group, a substituted or unsubstituted pyrazinyl group, a substituted or unsubstituted pyridyl group, or a substituted or unsubstituted benzimidazolyl group.

5. The compound according to claim 1, characterized in that Has the structure shown below, ; Here, D indicates that the hydrogen atom is deuterated.

6. Use of the compound according to any one of claims 1 to 5 in an organic electroluminescent device or an organic electroluminescent apparatus.

Citation Information

Patent Citations

  • Condensed ring compound and application thereof in organic electroluminescent device

    CN118063481A